Mengembangkan Kemampuan Menalar dan Memecahkan Masalah melalui Pembelajaran Berbasis Masalah (PBM) - E. Elvis Napitupulu (Study Program of Mathematics Education of Unimed Postgraduate Program, 2008)
Two of the five goals mandated by SBC to be achieved in the learning of mathematics in schools is to develop the ability to reason and solve problems. In addition to SBC also emphasizes math learning focus on solving problems. Reasoning and problem solving competence is a two occupying a central position in their respective roles. Reasoning ability is the main weapon to solve the problem while solving the problem is the main occupation in doing-math. For that it is a usual school curriculum models adopted to design and make room for math learning approach that promotes growth and blossoms both capacities. This paper highlights the importance of foster both competence is developed through the learning process in order to contribute to efforts to achieve national education goals.